Development of a Course on Cost-Benefit Analysis of Resilience Interventions - Kramer, Berber; Braun, Melody (2023)
This event introduced members of AICCRA cluster teams, and AICCRA collaborators in their networks with an interest in cost-benefit analysis, to a curriculum that has been developed based on the new methods for cost-benefit analysis in the CIS theme cluster. The event also introduced next steps, which include providing the full course to interested researchers, policymakers and practitioners working in the area of climate smart agriculture and climate information services, and working with participants on implementing their own cost-benefit analyses (proposed activities for the AF phase of AICCRA).